Myocardial capacity of mitochondrial oxidative phosphorylation in response to prolonged electromagnetic stress - Savchenko, Lesia; Martinelli, Ilenia; Marsal, Dimitri; Zhdan, Vyacheslav; Tao, Junwu; Kunduzova, Oksana (Frontiers in Cardiovascular Medicine, 2023)
Introduction Mitochondria are central energy generators for the heart, producing adenosine triphosphate (ATP) through the oxidative phosphorylation (OXPHOS) system. However, mitochondria also guide critical cell decisions and responses to the environmental stressors. Methods This study evaluated whether prolonged electromagnetic stress affects the mitochondrial OXPHOS system and structural modifications of the myocardium. To induce prolonged electromagnetic stress, mice were exposed to 915 MHz electromagnetic fields (EMFs) for 28 days. Results Analysis of mitochondrial OXPHOS capacity in EMF-exposed mice pointed to a significant increase in cardiac protein expression of the Complex I, II, III and IV subunits, while expression level of α-subunit of ATP synthase (Complex V) was stable among groups. Furthermore, measurement of respiratory function in isolated cardiac mitochondria using the Seahorse XF24 analyzer demonstrated that prolonged electromagnetic stress modifies the mitochondrial respiratory capacity. However, the plasma level of malondialdehyde, an indicator of oxidative stress, and myocardial expression of mitochondria-resident antioxidant enzyme superoxide dismutase 2 remained unchanged in EMF-exposed mice as compared to controls. At the structural and functional state of left ventricles, no abnormalities were identified in the heart of mice subjected to electromagnetic stress. Discussion Taken together, these data suggest that prolonged exposure to EMFs could affect mitochondrial oxidative metabolism through modulating cardiac OXPHOS system.